1995
DOI: 10.1029/94jc02392
|View full text |Cite
|
Sign up to set email alerts
|

The ocean response to operational westerly wind bursts during the 1991–1992 El Niño

Abstract: Numerical simulations of the remotely forced ocean response to westerly wind bursts prior to and during the 1991–1992 El Niño are examined; the models are forced by wind stress from the U.S. Navy's atmospheric global operational analysis/forecast system. The study focuses on (1) the relative response of the first and second internal modes to a single episode of westerly bursts; (2) the role of westerly bursts in producing the eastern Pacific sea level variations from October 1990 to February 1992; and (3) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…These shifts indxate eastward phase velocities of about 2.5 ms-', similar to those found in theoretical and modeling studies (e.g., Gill 1982;Geise and Harrison 1990;Kindle and Phoebus 1995). Correlations of the temperature time series in figure 2b with equatorial surface winds indicate that these Kelvin waves were initiated by eastward surface-wind anomalies, especially those associated with tropical cyclone winds, in the western Pacific.4 Figure 2b shows that the major Kelvin wave activity occurred in October 1991-April 1992 and October 1992-April 1993.…”
Section: B Thermal Anomalies In the Tropical Oceansupporting
confidence: 72%
See 1 more Smart Citation
“…These shifts indxate eastward phase velocities of about 2.5 ms-', similar to those found in theoretical and modeling studies (e.g., Gill 1982;Geise and Harrison 1990;Kindle and Phoebus 1995). Correlations of the temperature time series in figure 2b with equatorial surface winds indicate that these Kelvin waves were initiated by eastward surface-wind anomalies, especially those associated with tropical cyclone winds, in the western Pacific.4 Figure 2b shows that the major Kelvin wave activity occurred in October 1991-April 1992 and October 1992-April 1993.…”
Section: B Thermal Anomalies In the Tropical Oceansupporting
confidence: 72%
“…subsurface fluctuations was also a time of warm SSTs (28"-30°C) and positive SSTAs (1"-2"C; figures la, 2a -April 1993McPhaden 1993). The temporal and spatial patterns of these intraseasonal variations in upper-ocean temperature, along with current-velocity data (not shown), indicate internal equatorial ocean Kelvin waves (Kindle and Phoebus 1995;Murphree et aL3). Coriolis effects cause these waves to be confined within a few degrees of the equator and to propagate eastward along the equator (Gill 1982).…”
Section: B Thermal Anomalies In the Tropical Oceanmentioning
confidence: 99%
“…In contrast, Kindle and Phoebus (1995) suggested that a sloping thermocline increases the amplitudes of the SLA eld, basing their argument on the results from a study with a 1.5-layer ocean model. The situation is more complicated in a General Circulation Model (GCM) with a continuous strati cation, since the vertical extent of the waves is not limited to the surface layer de ned by the thermocline.…”
Section: Introductionmentioning
confidence: 93%
“…To further investigate the in uence of the oceanic background state on the IKWs, we carried out a set of numerical experiments with a highly resolved ocean model. These experiments have some similarities to Kindle and Phoebus (1995), who applied realistic wind forcing to an ocean model and studied the effect of a sloping thermocline on Kelvin wave amplitudes. We also attempted to elaborate on the previous studies by identifying the damping mechanisms that may take place during the different ENSO phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation